LONG-TERM CONSEQUENCES OF PATERNAL CANNABIS USE ON AUTISM CANDIDATE GENES. A CROSS-SECTIONAL STUDY PROPOSAL - Mădălina ZAHARIA (International Journal of Social and Educational Innovation, 2024)
The few existing studies concerning the effect of cannabis consumption on the male germ cells, generated sufficient evidence to indicate that paternal cannabis consumption might be involved in faulty sperm DNA methylation, at genes related to neurodevelopmental disorders, including ASD. Limitations of the exiting literature revolve around small sample sizes, insufficient reported data, unaccounted confounding variables and contradictory findings. The objective of this research proposal is to address current literature gaps and to bring clarification regarding previous findings, by using a larger sample size, and further explore the potential dose-effect relationship between cannabis exposure and the three ASD-related genes: DLGAP2, HCN1, and NR4A2. Our hypotheses assume that participants that have consumed cannabis for longer periods of time and in larger quantities will have higher levels of hypomethylation at these genes, comparing with the participants that have consumed less cannabis for shorter periods of times, or that haven't consumed at all. The results will push this emerging field further, and by extension, will generate more research questions, on topics like safety consumption thresholds, the permanence of epigenetic change and, if weather or not these changes can be inherited. Cumulated, the answers could possibly reshape preconception counselling advice offered to future fathers and influence the policy makers in prioritizing prevention efforts regarding hazardous cannabis consumption.